The Effects of Speed on the Running Performance of a Small Two-Wheeled Lunar Rover - Kimitaka Watanabe; Yamato Otani; Kazuto Tanaka (Aerospace)
Small wheeled lunar rovers tend to dig into surfaces via wheel rotation, causing them to slip and get stuck on regolith. Additionally, reducing power consumption remains a longstanding challenge. This study created a small two-wheeled rover and conducted tests at various wheel rotation speeds to assess the effects of rotation speed on its running performance. Through running tests and the measurement of reaction force, the influence of different wheel rotation speeds on running performance was clarified. Running at low rotation speeds prevented slipping and sinking. Additionally, the amount of sinkage was shown to converge to a certain level even at higher rotation speeds. These findings suggest that the maximum wheel rotation speed at which the rover avoids getting stuck allows the rover to achieve running with low-power consumption.